Loyalty program value: Give me more or treat me better? - Kwiatek, Piotr; Dženopoljac, Vladimir; Abdul, Rauf (Hotel and Tourism Management, 2021)
Customer loyalty programs are frequently used by companies to establish and improve relationships with customers by providing them with rewards. Loyalty programs investigated in the literature focus mainly on tangible rewards and economic benefits offered to the customers. However, some research done on intangible rewards of loyalty programs suggest that they can be superior to tangible benefits in affecting customer loyalty. Previous research drew conclusions in industry-specific settings. The aim of the paper is to assess the impact of tangible and intangible benefits on customer loyalty using an on-line customer panel representing different industries. The data collected from over 300 customers is subjected to CFA/SEM analysis in R environment. The main contribution of the present study is that it represents the first attempt (to the best of authors’ knowledge) to capture loyalty programs’ tangible and intangible value in an Arab cultural context, given the fact the focus was on the participants from the United Arab Emirates. Several important dimensions of LP programs in an Arab country are revealed. Firstly, the study confirmed that social value of a loyalty program significantly impacts customer loyalty. In addition, it was confirmed that the flexibility of a loyalty program increased customer loyalty. Ultimately, it was established that customers value intangible benefits more than the tangible ones.